1997
DOI: 10.1136/vr.140.25.654
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem comparison of ultrasonography, endocrine measurements and histology of large abnormal ovarian follicles in cows

Abstract: Six saprophytic A invadans Aphanomyces isolates species Four A astaci isolates Two UM Aphanomyces isolates FIG 1: Average similarity coefficients (F ± sd) of A invadans in comparison with other Aphanomyces isolates calculated from RAPD band patterns all the A invadans isolates had identical nucleotide sequences within the 18S nuclear rRNA gene region and could not be differentiated by restriction fragment length polymorphism (RFLP) analyses of the less-conserved internally transcribed spacer (ITS) regions, loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…36 Thickwalled cyst produce progesterone whereas thin-walled cyst in the absence of other follicles of more than 5mm diameter produce estradiol, but thin-walled cyst in the presence of other follicles of more than 5mm diameter are not estrogenic. [44][45][46] All thick-walled cysts should respond immediately to PGF 2 α. 35 On the other hand, Tebble et al, 37 found no influence of follicular cyst wall thickness on the outcome of treatment either with GnRH or PRID.…”
Section: Discussionmentioning
confidence: 99%
“…36 Thickwalled cyst produce progesterone whereas thin-walled cyst in the absence of other follicles of more than 5mm diameter produce estradiol, but thin-walled cyst in the presence of other follicles of more than 5mm diameter are not estrogenic. [44][45][46] All thick-walled cysts should respond immediately to PGF 2 α. 35 On the other hand, Tebble et al, 37 found no influence of follicular cyst wall thickness on the outcome of treatment either with GnRH or PRID.…”
Section: Discussionmentioning
confidence: 99%
“…Wall thickness is much less in follicular cysts (average of 2.5 mm, range 1-6 mm) than in luteal cysts (5.3 mm, range 3-9 mm; Douthwaite and Dobson, 2000). With follicular cysts, there appears to be a correlation between ultrasonographic wall thickness and hormone concentrations within that cyst, with thicker-walled cysts (average 2.5 mm) showing high progesterone and low oestradiol concentrations, and vice versa in thinner-walled cysts (average 1.3 mm; Scott and Dobson, 1997).…”
Section: Rectal Ultrasonography (Figs 3-6)mentioning
confidence: 99%
“…Typically, the follicular cyst does not require treatment in these cases, as it is physically present but exerts no hormonal influence. A study by Scott and Dobson (1997), however, suggests that the corpus luteum does not influence the steroid concentrations within a follicular cyst. The practical relevance of this needs clarification.…”
mentioning
confidence: 97%
“…OC result in prolongation of the calving interval, reduced milk production, increased culling rates (Bartlett et al, 1986;Fourichon et al, 2000) with significant economic losses to the dairy farmer (Scott and Dobson, 1997;.…”
Section: Introductionmentioning
confidence: 99%